Incentives dominate selection: Chamber-changing legislators are driven by electoral rules and voter preferences - Marco Portmann; David Stadelmann; Reiner Eichenberger (ZBW - Leibniz-Informationszentrum Wirtschaft, 2019)
The role of electoral incentives vs. selection is ideally analyzed in a setting where the same legislators are selected to decide on policies under different electoral rules and where voter preferences on policies can be precisely measured. This is the first paper to look at such a situation. The institutional setting of Switzerland allows us to observe the behavior of legislators who change from a proportionally-elected chamber to a majority-elected chamber of parliament with their electorate being the same in both chambers. Voter preferences are revealed in a large number of referenda. We causally identify behavioral changes of legislators who are chamber-changers in comparison to other legislators due to the respective electoral rules along three dimensions, all measured at the level of individual legislators: representation of revealed voter preferences for policies, party loyalty, and interest group affiliations. The evidence suggests that electoral incentives explain the behavioral response of chamber-changers towards voter preferences to such an extent that there remains no role for selection. Chamber-changers become less loyal towards their party and adapt their lobby group affiliations towards more district-oriented interests after having changed from a proportionally-elected chamber to a majority-elected chamber.
Keywords: D72; P16; 330; Preference representation; elections; incentives; electoral systems; voting; political presentation; responsiveness; legislative behavior; electoral connection.